Language and Gender: The Secret Behind Willa Cather’s Use of a Male Narrator in my Antonia - Rawiya Kouachi (The Journal of Studies in Language, Culture and Society, 2018)
The research seeks to show how language can unravel issues relevant to an author’s identity and gender. It is an analytical study from a biographical perspective of Willa Cather’s novel My Antonia. It aims at showing how Cather’s language can help in revealing something about her identity. The study investigates the reason behind Cather’s use of a male narrator, Jim Burden, in a novel written by a woman and it is about a female character Antonia. The analysis shows that the secret behind Cather’s use of a male narrator is her lesbian identity and through the use of a male narrator, she hides her lesbianism. Consequently, Cather’s language exposes her gender identity and proves that an author’s language can help in decoding something about his/her identity especially in modern times where the distinct gender boundaries are violated.